(untitled) (Research, Society and Development, 2022)
Objective: To map the existing scientific evidence on the early identification of Autism Spectrum Disorder (ASD) in children in Primary Health Care. Review Method: Scoping review protocol according to the Joanna Briggs Institute (JBI) method, will meet the Preferred Reporting Items for Systematic Reviews and Meta-analyses Scoping Review (PRISMA-ScR). Published and unpublished bibliographic materials will be considered, according to the following inclusion criteria: reporting on the early identification of Autism Spectrum Disorder (concept) in children (population) in Primary Care (context). A detailed search strategy will be used for the bases and/or databases: Virtual Health Library (VHL), PubMed and LILACS, with no time limit. Titles and abstracts will be screened by two reviewers, who will read the full texts and extract data from the included material, after which evidence of the results will be synthesized and presented in a narrative form. Presentation and Interpretation of Results: The results included will be classified into conceptual analysis categories based on the Thematic Categorical Analysis, based on Bardin’s content analysis.